2000
DOI: 10.1590/s0004-282x2000000400003
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density, vitamin D and anticonvulsant therapy

Abstract: -The aim of this study was to assess bone mineral density and vitamin D metabolism in patients on chronic anticonvulsant therapy. Methods: Sixty-nine men, outpatients on chronic anticonvulsant therapy, who had been treated for at least 5 years, were studied, comparing them to thirty healthy controls. Bone mineral density was measured as well as serum levels of calcium, ionized calcium, alkaline phosphatase, PTH, 25-hydroxycholecalciferol and 1,25-dihydroxycholecalciferol. Results: No differences in bone minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 11 publications
0
22
1
3
Order By: Relevance
“…Other studies in more sunny regions, where the dermal production of the vitamin D precursor was normal, showed neither hypovitaminosis D nor abnormalities of bone metabolism in epileptic patients 9,28 . For example, male AED users in Campinas (latitude 20 -24 degrees South) showed no difference between BMD, 25OHD and 1,25OHD of patients when compared to a control group matched by age and BMI 9 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Other studies in more sunny regions, where the dermal production of the vitamin D precursor was normal, showed neither hypovitaminosis D nor abnormalities of bone metabolism in epileptic patients 9,28 . For example, male AED users in Campinas (latitude 20 -24 degrees South) showed no difference between BMD, 25OHD and 1,25OHD of patients when compared to a control group matched by age and BMI 9 .…”
Section: Discussionmentioning
confidence: 82%
“…Studies indicate that 20 to 60% of AED users can develop rickets or osteomalacia, especially among older and institutionalized patients. However, in outpatient populations, some studies have not demonstrated a deleterious effect of AED on bone metabolism [7][8][9] . Drugs such as CBZ, PB, PRM and DPH are known to induce hepatic mixed function oxidase activity throughout the microsomal enzymes (P450) in the liver.…”
Section: Palavras-chave: Drogas Antiepiléticas Indutoras Hepáticas 2mentioning
confidence: 99%
“…Exposure of arm and face skin to sunlight for 30min supplies the daily amount of vitamin D the body needs 1,39 . In Brazil, located at a latitude below 24ºS, the plasmatic levels of 25(OH) D and 1.25(OH) 2 D were normal in both healthy men and in epileptics using anticonvulsive drugs, which reduce these levels 64 .…”
Section: Vitamin Dmentioning
confidence: 94%
“…It has been reported that antiepileptic drugs might predispose to bone fractures in patients by decreasing the BMD [12][13][14][15]. Osteomalacia or osteoporosis developing in patients using antiepileptic drugs can present, with radiological, biochemical and pathological findings.…”
Section: Discussionmentioning
confidence: 99%
“…They may therefore cause important changes in adolescents during pubertal development and on fertility. Additionally, it has been known for over 30 years that some antiepileptic drugs have predisposed patients to bone fractures by decreasing bone mineral density (BMD) [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%